COMPARATIVE CHARACTERISTICS OF ENTERPRISES IN RUSSIA AND FOREIGN COUNTRIES - Marina Ribasova (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the activities of enterprises in Russia and foreign countries. The author noted that the effective operation of enterprises is determined by many circumstances, among which the most important should be considered a high degree of uncertainty and unpredictability of the economic situation in the country due to the introduction of sanctions, the difficult economic situation of most enterprises, a lot of contradictions within the enterprises themselves. The article proves that business carries a powerful potential, forming a competitive environment, creating and maintaining innovative activity, performing a huge number of functions in the economy of Russia and foreign countries.